2005
DOI: 10.1510/icvts.2005.106914
|View full text |Cite
|
Sign up to set email alerts
|

Role of video-assisted thoracic surgery in the evaluation and management of thoracic injuries

Abstract: The aim of this study was to evaluate the experience of our institution with the use of video-assisted thoracic surgery (VATS) in chest trauma. Between January 1999 and September 2004, 25,213 patients presented with chest trauma to the emergency room, and 2304 were admitted to our service. Twenty-three hemodynamically stable patients (1%) underwent VATS. They were 19 men and 4 women with an average age of 42 years (range, 19-67 years). Indications included post-traumatic hemothorax in 11 patients, and post-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…VATS can provide complete visualization of intrathoracic organs including diaphragm, pericardium and mediastinum [5][6][7]. Therefore, VATS was mainly used for evacuation of retained hemothorax, wedge resection of lung, decortication of empyema and repair of diaphragm [5,6,10,11]. Our results were similar to the previous reports: operative procedures included evacuation of clotted hemothorax (3 cases), wedge resection (3 cases), adhesiolysis and decortication (2 cases), hemostasis of intrathoracic bleeders (1 case), repair of diaphragm (1 case) and suture repair of the lacerated lung (1 case).…”
Section: Discussionmentioning
confidence: 99%
“…VATS can provide complete visualization of intrathoracic organs including diaphragm, pericardium and mediastinum [5][6][7]. Therefore, VATS was mainly used for evacuation of retained hemothorax, wedge resection of lung, decortication of empyema and repair of diaphragm [5,6,10,11]. Our results were similar to the previous reports: operative procedures included evacuation of clotted hemothorax (3 cases), wedge resection (3 cases), adhesiolysis and decortication (2 cases), hemostasis of intrathoracic bleeders (1 case), repair of diaphragm (1 case) and suture repair of the lacerated lung (1 case).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers (3,5) believe that the ease and practicality of video-assisted thoracoscopy, as compared with thoracotomy, should not be used as the principal argument in favor of the removal of intrathoracic bullets.…”
Section: Discussionmentioning
confidence: 99%
“…In the late phase, usually, the irritation process causes fibrous adherences that have the end result of lodging the foreign body in the point of greatest declination. (4,5) In our two patients, the X-rays were taken in the acute phase, when the bullets were still free in the pleural cavity. In Case 2, the bullet was thought to be located in the abdomen.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…There was no mortality and complications occurred in three patients (13%). Potaris et al [45] concluded that VATS provides diagnostic accuracy and therapeutic efficacy in hemodynamically stable patients with thoracic injuries.…”
Section: Diagnostic Studiesmentioning
confidence: 99%